2019
DOI: 10.1080/20008198.2018.1558705
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and the role of self-blame on psychological well-being after deployment in male veterans

Abstract: Background: Childhood trauma and combat-related trauma are both associated with decreased psychosocial functioning. Coping strategies play an important role in the adjustment to traumatic events.Objective: The present study examined childhood trauma and the mediating role of coping strategies in adult psychological symptoms in a non-clinical military population after deployment to Afghanistan. Additionally, the moderating role of coping strategies in vulnerability to combat events was explored.Method: Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The clear link between childhood trauma and post-deployment increase in depression symptoms (Low-increasing trajectory membership), even with the inclusion of combat exposure, PTSD symptoms and social support at homecoming, supports the notion that early adversity is related to the course of depression (Jaworska-Andryszewska and Rybakowski, 2019; Spinhoven et al, 2011). Indeed, the fact that a rise in depression symptoms is seen in the wake of deployment in this trajectory, suggests that childhood trauma might act as a stress sensitizer to increase the risk of depression following deployment (Bandoli et al, 2017;Cabrera et al, 2007;Dorresteijn et al, 2019;Hammen et al, 2000;Rudenstine et al, 2015). However, we found no interaction between childhood trauma and combat exposure, indicating that it might not be the interaction between childhood trauma and combat exposure per se that explains the rise in depression symptoms for this group, but childhood trauma in combination with the general toll of deployment.…”
Section: Discussionmentioning
confidence: 56%
“…The clear link between childhood trauma and post-deployment increase in depression symptoms (Low-increasing trajectory membership), even with the inclusion of combat exposure, PTSD symptoms and social support at homecoming, supports the notion that early adversity is related to the course of depression (Jaworska-Andryszewska and Rybakowski, 2019; Spinhoven et al, 2011). Indeed, the fact that a rise in depression symptoms is seen in the wake of deployment in this trajectory, suggests that childhood trauma might act as a stress sensitizer to increase the risk of depression following deployment (Bandoli et al, 2017;Cabrera et al, 2007;Dorresteijn et al, 2019;Hammen et al, 2000;Rudenstine et al, 2015). However, we found no interaction between childhood trauma and combat exposure, indicating that it might not be the interaction between childhood trauma and combat exposure per se that explains the rise in depression symptoms for this group, but childhood trauma in combination with the general toll of deployment.…”
Section: Discussionmentioning
confidence: 56%
“…The literature, in this context, has addressed self-blame as a consequence of abusive incidents and as something that has far-reaching effects on the lives of children in both childhood and adulthood. For example, Dorresteijn et al (2019) demonstrated how childhood trauma is related to adult symptoms of general anxiety, depression, and problems concerning interpersonal sensitivity through the mediation of self-blame as a coping strategy. Other findings have also demonstrated that self-blame is particularly relevant for the onset of post-traumatic stress disorder following sexual assault (Kline et al, 2018) and plays a significant role in other ramifications, such as negative social reactions (Ullman & Filipas, 2005), revictimization during adulthood (Filipas & Ullman, 2006), internalized stigma (Kennedy & Prock, 2018), and psychopathology (Whiffen & MacIntosh, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism through which pre-school children could develop PTG is through interaction with parents. Pre-school years is deemed a very sensitive period and an age where war exposure may persist throughout life (Leon 2012;Currie and Vogl 2013;Arroyo and Eth 1996;Pynoos and Nader 1993), because of-among other mechanisms-psychological distress (Kijewski and Freitag 2016), confusion, and self-blame (Dorresteijn et al 2019). These reactions might be magnified by children's perception that caregivers where stressed or extremely worried during traumatic events.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%